THz birefringence inside femtosecond laser filament in air. (September 2021) - Yu, Zhiqiang; Su, Qiang; Zhang, Nan; Gao, Hui; Zhang, Zhi; Chu, Chunyue; Xu, Qiang; Zhang, Yang; Liu, Weiwei
Highlights: Large birefringence of THz wave inside a femtosecond laser filament was observed. The birefringence is attributed to the strong confinement of THz wave inside the filament. THz wave with arbitrary polarization orientation, ellipticity and chirality can be produced. Abstract: Large birefringence of THz wave inside a femtosecond laser filament in air has been found in this work. By varying the laser pulse energy, the filament length is changed, inducing variation in the phase delay between two perpendicularly polarized THz pulses. The birefringence could be explained by the delayed rotational molecular wave packet of air molecules inside the femtosecond laser-induced filament. The newly discovered THz birefringence is essentially attributed to the strong confinement of the THz pulse inside the filament. This phenomenon has opened a new way to freely control the polarization of THz pulses emitted from an optical filament and significantly benefits polarization-sensitive THz spectroscopy and control of matter.